Criterio que aplica el Ministerio Público al momento de calificar el delito de fuga por accidente de tránsito y omisión de socorro, cuando los hechos se derivan de un accidente de tránsito en el distrito fiscal de Loreto–periodo-2019 - Flores Villacres, Marcos Eduardo (2025)
The crime of escape due to a traffic accident and omission of relief are the crimes that derive from a traffic accident. For the majority of prosecutors, the existence of the actual crime contest, however, for another sector, the ideal contest of crimes and apparent norms contest. As a result of this investigation, another legal investigation was born regarding the crime of omission of relief. The objective of the present investigation is to determine the criteria of the representative of the public ministry, when qualifying the crime of flight due to a traffic accident and omission of relief, when the facts derive from a traffic accident, for them it was carried out the research of the type of scriptive and applicative, due to the fact that the characteristic features of the study objective were described. The investigation concludes that the representative of the public ministry at the time of qualifying the moment of escape due to a traffic accident and omission of relief, when the facts derive from a traffic accident, it was determined that the criterion is the literal interpretation of the actual contest of crimes; however due to strategy, they do not apply the extenciba interpretation, because only the crimes of serious injuries and/or negligent omission and escape due to a traffic accident would be being investigated, due to an ideal competition of crimes or apparent competition of the norms.